Nature and Properties of Lateritic Soils Derived from Different Parent Materials in Taiwan. (24th April 2014) - Ko, Tzu-Hsing
Abstract : The objective of this study was to investigate the physical, chemical, and mineralogical composition of lateritic soils in order to use these soils as potential commercial products for industrial application in the future. Five lateritic soils derived from various parent materials in Taiwan, including andesite, diluvium, shale stone, basalt, and Pleistocene deposit, were collected from the B t 1 level of soil samples. Based on the analyses, the Tungwei soil is an alfisol, whereas other lateritic soils are ultisol. Higher pH value of Tungwei is attributed to the large amounts of Ca 2+ and Mg 2+ . Loupi and Pingchen soils would be the older lateritic soils because of the lower active iron ratio. For the iron minerals, the magnetic iron oxides such as major amounts of magnetite and maghemite were found for Tamshui and Tungwei lateritic soils, respectively. Lepidocrocite was only found in Soka soil and intermediate amounts of goethite were detected for Loupi and Pingchen soils. After Mg-saturated and K-saturated processes, major amounts of mixed layer were observed in Loupi and Soka soils, whereas the montmorillonite was only detected in Tungwei soil. The investigation results revealed that the parent materials would play an important role during soil weathering process and physical, chemical, and mineralogy compositions strongly affect the formation of lateritic soils.